2015
DOI: 10.1149/2.0921603jes
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of “Effective pH” on the Voltammetric Behavior ofp-Benzoquinone and Hydroquinone in Acetonitrile

Abstract: Brønsted–Lowry acids and bases exert important effects on the electrochemistry of hydroquinone (QH2) and benzoquinone (Q) in acetonitrile. However, the “effective pH” in aprotic media has been neglected in the redox process of QH2 and Q. Our results show that neutral proline induces new voltammetric waves for QH2 and quinone in acetonitrile, that cannot be attributed to protonation or hydrogen bonding. We observed that only one cathodic wave and one anodic wave of quinone are produced in adequately buffered ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A study on the effects of hydrogen bonds in different Q/HQ systems in non-aqueous media showed that the presence of oxygenated functional groups on the surface of the electrode could affect the interaction between dissolved compounds and the surface, which had a significant impact on the electron transfer process [ 23 ]. The electrochemistry of quinones in the presence of added hydroquinone as a hydrogen bonding proton donor, the effective pH at the electrode surface [ 24 ] as well as the electrochemical effect of CO 2 in dimethylformamide solution, were all studied [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study on the effects of hydrogen bonds in different Q/HQ systems in non-aqueous media showed that the presence of oxygenated functional groups on the surface of the electrode could affect the interaction between dissolved compounds and the surface, which had a significant impact on the electron transfer process [ 23 ]. The electrochemistry of quinones in the presence of added hydroquinone as a hydrogen bonding proton donor, the effective pH at the electrode surface [ 24 ] as well as the electrochemical effect of CO 2 in dimethylformamide solution, were all studied [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have attributed the appearance of a pre-wave to the local modification of the effective pH on the surface of the electrode. 43 This option, however, does not seem to fit our results because the appearance of a new diffusion-limited wave at slow scan rates (Fig. 8b) indicates the formation of a reasonably stable reducible species.…”
Section: Ddqmentioning
confidence: 74%
“…It should be noted that this reduction on a regular glassy carbon cathode displays normal reversibility. [57] Methyl viologen was scanned to the second electron transfer in bulk and past the first in the flat cell. The peak splitting of the first wave was equivalent for both measurements (120 mV) and the currents were comparable.…”
Section: Electrochemical Validationmentioning
confidence: 99%